Pengaruh Struktur Industri Regional Dan Penanaman Modal Asing (PMA) Terhadap Pertumbuhan Produktivitas Industri Indonesia - Indi Sutopo; Endang Setiasih (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2012)
Productivity performance is the key to improving the country's living standards. From this perspective, productivity improvement should not only be the goal of the business community, but of all groups in society. This research examines the impact of the characteristics industrial regional structure and the Foreign Direct Investment (FDI) to productivity growth in Indonesia. This study find that the impact of investment per employee and regional competition structure, a positive and statistically significant. Finally, intra industry spillovers from FDI are found at the national level and there are the positive and significant correlation between FDI and Domestic investment to the other larges industrial in Indonesia. Keywords:productivity, industry, investment